2022
DOI: 10.1186/s12917-022-03522-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mRNA and miRNA in the response to Salmonella enterica serovar Enteritidis infection in chicken cecum

Abstract: Background Salmonella enterica, serovar Enteritidis (SE) is a food-borne pathogen, which can cause great threat to human health through consumption of the contaminated poultry products. Chicken is the main host of SE. The mRNA and microRNA (miRNA) expression profiles were analyzed on cecum of Shouguang chicken via next-generation sequencing and bioinformatics approaches. The treated group was inoculated SE, and the control group was inoculated with phosphate buffer saline (PBS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…These receptors are mainly involved in the recognition of diacylated or triacylated bacterial lipopeptides, 36 and Higuchi et al reported that chTLR2a/chTLR1b heterodimer was activated by peptidoglycan 37 . In the present study, the expression of TLR1a, TLR1b, TLR2a and TLR2b was all significantly upregulated in cecum of the chicken infected with E. tenella , which was consistent with Miao's research of the four chTLRs showed a significant upregulation in the cecum of chickens during infection with S. enterica 38 . These increased gene expression may facilitate an increased recognition of lipoproteins and peptidoglycan.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These receptors are mainly involved in the recognition of diacylated or triacylated bacterial lipopeptides, 36 and Higuchi et al reported that chTLR2a/chTLR1b heterodimer was activated by peptidoglycan 37 . In the present study, the expression of TLR1a, TLR1b, TLR2a and TLR2b was all significantly upregulated in cecum of the chicken infected with E. tenella , which was consistent with Miao's research of the four chTLRs showed a significant upregulation in the cecum of chickens during infection with S. enterica 38 . These increased gene expression may facilitate an increased recognition of lipoproteins and peptidoglycan.…”
Section: Discussionsupporting
confidence: 91%
“…37 In the present study, the expression of TLR1a, TLR1b, TLR2a and TLR2b was all significantly upregulated in cecum of the chicken infected with E. tenella, which was consistent with Miao's research of the four chTLRs showed a significant upregulation in the cecum of chickens during infection with S. enterica. 38 These increased gene expression may facilitate an increased recognition of lipoproteins and peptidoglycan.…”
Section: Changes In Hdp Gene Expression In the Caecum Of E Tenella-in...mentioning
confidence: 99%